2003
DOI: 10.1111/j.1464-0597.2004.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Subjective Mental Workload: A Comparison of SWAT, NASA‐TLX, and Workload Profile Methods

Abstract: Cette recherche mesure plusieurs propriétés psychométriques (l'ingérence, la sensibilité, la valeur diagnostique et la validité) de trois instruments multidimensionnels de l'évaluation de la charge de travail subjective: le NASA Task Load Index (TLX), le Subjective Workload Assessment Technique (SWAT) et le Workload Profile (WP). Sujets ont réalisé deux tâches de laboratoire séparé-ment (tâches simples) et simultanément (tâches doubles). D'après l'analyse de variance, les trois instruments ne présentent pas de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
391
1
22

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 656 publications
(419 citation statements)
references
References 23 publications
5
391
1
22
Order By: Relevance
“…The following formula was used to determine the sample volume:, in which Z is confidence coefficient (equal to 95% confidence), The second part of the questionnaire assessed the mental work load status using the assessment scale of the NASA-TLX, one of the most commonly used tools to evaluate mental workload in terms of individual perspective (Cao et al, 2009;Holden et al, 2010;Holden et al, 2011;Safari et al, 2013). Several reports have confirmed the reliability and validity of NASA-TLX to evaluate mental workload (Hoonakker et al, 2011;Rubio et al, 2004); for instance, Hoonakker et al (2011) reported the appropriateness of convergent and discriminant validities of the NASA mental workload scale (Hoonakker et al, 2011). Mohammadi et al (2013) approved the validity of the Persian version of the questionnaire, and its internal consistency reliability (Cronbach's alpha) of 0.847 was estimated to be suitable .…”
Section: Materials-methodsmentioning
confidence: 99%
“…The following formula was used to determine the sample volume:, in which Z is confidence coefficient (equal to 95% confidence), The second part of the questionnaire assessed the mental work load status using the assessment scale of the NASA-TLX, one of the most commonly used tools to evaluate mental workload in terms of individual perspective (Cao et al, 2009;Holden et al, 2010;Holden et al, 2011;Safari et al, 2013). Several reports have confirmed the reliability and validity of NASA-TLX to evaluate mental workload (Hoonakker et al, 2011;Rubio et al, 2004); for instance, Hoonakker et al (2011) reported the appropriateness of convergent and discriminant validities of the NASA mental workload scale (Hoonakker et al, 2011). Mohammadi et al (2013) approved the validity of the Persian version of the questionnaire, and its internal consistency reliability (Cronbach's alpha) of 0.847 was estimated to be suitable .…”
Section: Materials-methodsmentioning
confidence: 99%
“…Mental work load is used as a valid and reproducible indicator for human/machine interface development and comparison. 12,13 Mental work load monitoring enables the depiction of differences that will not be observed when using standard objective and subjective tests. NASA-TLX is a multidimensional tool that was developed by the National Aeronautics and Space Administration's Ames Research Center in 1986 and validated in 1988 for perceptual work load evaluations using task-load index (TLX) measurement.…”
Section: Mental Work Load Evaluationmentioning
confidence: 99%
“…At the end of each trial, participants were asked to fill a NASA Task Load Index (TLX) questionnaire [18] for each action performed on the drones. This questionnaire was exploited to evaluate operators' self-assessed workload on a six-dimensions scale regarding: mental demand, physical demand, temporal demand, performance, effort, and frustration, with a score from 0 to 100.…”
Section: Resultsmentioning
confidence: 99%